Responsabilidade social empresarial (RSE) na Suécia, Tailândia e Brasil: uma abordagem comparativa em empresas de construção civil - Wottrich, Vanessa Hastenpflug (2008)
Corporate social responsibility (CSR) has recently been the subject of increased attention, both in the academic and the corporate arena. In practice, corporations define their approach to CSR by using their own lenses, being influenced by factors at regional, national, industrial and corporate levels. This study aims at identifying how the largest companies in the construction industry in Sweden, Thailand and Brazil present themselves in terms of CSR. Although there is an increasing pressure on corporations to play a more explicit role in the welfare of society and the importance of behaving socially responsibly is well accepted in the literature, there have been very few attempts at identifying how companies from different geographical regions themselves define and interpret CSR. The construction industry is acknowledged as problematic in terms of social and environmental impact, being also one of the largest industries worldwide in terms of participation in the GNP of most countries. The research was carried out through the analysis of organizational documents from the largest companies in the construction industry of the abovementioned countries. The model proposed by Silberhorn and Warren (2007) was used for data collection purposes, including CSR Principles, Processes and Stakeholder Issues. The analysis of results was carried out through cross-national comparisons among countries according to the researched categories, as well as the identification of factors shaping the differences and similarities among countries. Results suggest a predominant CSR value-driven approach, which might indicate that CSR has come a long way from its early roots of charity to become a strategic business practice inserted in corporate values. Although the cross-national differences were apparently mainly shaped by regional factors, the industry sector has emerged as an important factor shaping the areas of cross-national agreement.